Cellular stress promotes NOD1/2‐dependent inflammation via the endogenous metabolite sphingosine‐1‐phosphate. (4th May 2021) - Pei, Gang; Zyla, Joanna; He, Lichun; Moura‐Alves, Pedro; Steinle, Heidrun; Saikali, Philippe; Lozza, Laura; Nieuwenhuizen, Natalie; Weiner, January; Mollenkopf, Hans‐Joachim; Ellwanger, Kornelia; Arnold, Christine; et al.
Abstract: Cellular stress has been associated with inflammation, yet precise underlying mechanisms remain elusive. In this study, various unrelated stress inducers were employed to screen for sensors linking altered cellular homeostasis and inflammation. We identified the intracellular pattern recognition receptors NOD1/2, which sense bacterial peptidoglycans, as general stress sensors detecting perturbations of cellular homeostasis. NOD1/2 activation upon such perturbations required generation of the endogenous metabolite sphingosine‐1‐phosphate (S1P). Unlike peptidoglycan sensing via the leucine‐rich repeats domain, cytosolic S1P directly bound to the nucleotide binding domains of NOD1/2, triggering NF‐κB activation and inflammatory responses. In sum, we unveiled a hitherto unknown role of NOD1/2 in surveillance of cellular homeostasis through sensing of the cytosolic metabolite S1P. We propose S1P, an endogenous metabolite, as a novel NOD1/2 activator and NOD1/2 as molecular hubs integrating bacterial and metabolic cues. Synopsis: Cellular stress induces inflammatory responses, however precise mechanisms remain unknown. We show that various stimuli, including disruption of cytoskeleton, ER stress, Golgi stress, mitochondrial stress or DNA damage, all converge in the accumulation of the endogenous lipid metabolite sphingosine‐1‐phosphate (S1P) in the cytosol. Subsequently, S1P binds to and activates NOD1/2 resulting in inflammatory responses. Various types of cellular stress trigger NOD1/2 activation and the release of inflammatory cytokines/chemokines. Cytosolic S1P is mainly generated via the hydrolysis pathway upon perturbation of cellular homeostasis. S1P directly binds to NOD1/2 via the NBD domains, impairing ADP binding to NOD1/2. S1P induces NOD1/2‐RIP2 dependent NF‐κB and MAPK activation. Abstract : Intracellular pattern recognition receptors NOD1/2, best known as sensor of bacterial peptidoglycans, can also be directly activated by signaling lipid sphingosine‐1‐phosphate accumulating upon perturbed cellular homeostasis, thus linking general stress to inflammatory responses.